2018
DOI: 10.1039/c8ta04098b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of perfluorinated ionomer in PEDOT:PSS on the rectification and degradation of organic photovoltaic cells

Abstract: Poly (3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is widely used to build optoelectronic devices. However, as a hygroscopic waterbased acidic material, it brings major concerns for stability and degradation, resulting in an intense effort to replace it in organic photovoltaic (OPV) devices. In this work, we focus on the perfluorinated ionomer (PFI) polymeric additive to PEDOT:PSS. We demonstrate that it can reduce the relative amplitude of OPV device burn-in, and find two distinct regimes of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 179 publications
(201 reference statements)
0
17
0
Order By: Relevance
“…[ 14,17,30 ] Currently, the best polymer donor reported for collocating NFAs requires an extremely deep highest occupied molecular orbital ( HOMO ) level that is more negative than −5.4 eV to maximize the built‐in voltage of devices. [ 9–11,16,17,31 ] The low HOMO level of the active layer therefore forms a massive energy barrier between the HOMO of the electron donor and the work function (WF) of PEDOT:PSS (WF ≈ −5.0 eV is mostly reported in the literature), [ 32–34 ] which results in the poor electrical performance of inverted devices. Nevertheless, only a few studies have reported an inverted OPV device using an NF‐based BHJ layer with an alternative solution‐processed HTL for industrial module production.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14,17,30 ] Currently, the best polymer donor reported for collocating NFAs requires an extremely deep highest occupied molecular orbital ( HOMO ) level that is more negative than −5.4 eV to maximize the built‐in voltage of devices. [ 9–11,16,17,31 ] The low HOMO level of the active layer therefore forms a massive energy barrier between the HOMO of the electron donor and the work function (WF) of PEDOT:PSS (WF ≈ −5.0 eV is mostly reported in the literature), [ 32–34 ] which results in the poor electrical performance of inverted devices. Nevertheless, only a few studies have reported an inverted OPV device using an NF‐based BHJ layer with an alternative solution‐processed HTL for industrial module production.…”
Section: Introductionmentioning
confidence: 99%
“…19,[23][24][25][26][27] Although p-type organic semiconductors are generally regarded as air-stable, there are a few degradation pathways such as water absorption and diffusion of molecules with small sizes or low boiling point, which leads to the creation of trap states or morphological changes in the microstructure of the OSC. [28][29][30] Formic acid (FA) is a common dopant for PEDOT:PSS, which makes a clear example of such a mechanism. Its low boiling point leads to evaporation of the FA and thus losses in electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The W F of PEDOT:PSS mixed with PFI increased from 4.71 to 5.41 eV, which leads to the subtle increase in V OC from 0.59 to 0.62 V for P3HT:PC 61 BM based OSCs. [255] For PerSCs, PFI-PEDOT:PSS displayed improved V OC of 0.05-0.15 V. [256,257] However, it should be noted that the increased work function does not necessarily improve the V OC . Interaction between HTL and active layer is important for charge collection.…”
Section: Modification Of Pedot Htlmentioning
confidence: 99%